Expression Activity of Selected Proangiogenic Factors in Patients with Limb Ischemia - Miroslava, RabajdovA; Marian, Tomecko; Vladimira, Tomeckova; Zuzana, Gul'asova; Ivana, Spakova; Vladimir, Komanicky; Maria, Marekova; Frantisek, Sabol (Current Metabolomics, 2018)
Background: Blood plasma/serum is a characteristic mixture of naturally occurring endogenous fluorophores which are sensitive to endogenous and exogenous stress during physiological as well as pathological processes in the body. Methods: The structure of the patient's blood plasma/serum surfaces with critical limb ischemia and healthy subjects were studied and compared using methods of synchronous fluorescence fingerprint and atomic force microscopy, which are usually not used in clinical practice. The molecules of IGF-2, HIF-1 and VEGF-A in the blood vessels of patients with a critical ischemic limb during the surgery were analyzed by qRT-PCR and electrophoretic detection. Results: Angiogenesis and also ischemia were detected in the ischemic blood vessels tissue of patients as a significant increased expression of mRNA levels of HIF-1 and VEGF-A genes in comparison with healthy subjects. The increased fluorescence intensity of proteins at wavelength λ = 280 nm/Δ60 nm was observed in the blood plasma/serum of patients. The fluorescence spectroscopy and atomic force microscopy revealed that the ischemic blood plasma and serum contains changed structures of proteins. Conclusion: Spectroscopic signals can study ischemic changes and these can generally predict morphological changes in the blood plasma/serum. Atomic force microscopy investigated structural changes of proteins in the blood plasma/serum. Methods of molecular analysis detected significant hypoxia in the blood tissue as significant increase of HIF-1 molecule and simultaneously significant angiogenesis as a significant increase of VEGF-A molecules. New nontraditional techniques may contribute to early diagnosis of the various vascular diseases in patients in future.
Keywords: proteins